CAN MUSLIM INHERIT BITCOIN? DISCOVERING THE CONTINUITY OF DIGITAL ASSET IN PERLIS (International Journal of Islamic Business, 2022)
Day by day the numbers of Bitcoins owners are increasing and as the time lapses, they also will face the death. In Perlis, Bitcoins is recognised as a wealth (mal) and subject to zakat by State Fatwa Committee of Perlis. Hence, this paper aims to discover the inheritability of bitcoin according to Shariah in Perlis. As a result, this study employed a qualitative research approach by interview in order to discover the inheritability of bitcoin as a mal according to Shariah. Purposive sampling was used in the study. The finding of this study indicated that the existing fatwa on bitcoin is silent on the inheritance ruling of bitcoin. The researcher urged that this inheritance ruling must be tabled and gazetted by the state fatwa committee of Perlis in order to ensure the continuity of bitcoin to the next generation. Therefore, this study has contributed in comprehensive Shariah views behind the permissibility of Bitcoin in Perlis and provides some important policy implication for the regulator and state fatwa committee of Perlis to fulfil the lacuna in the fatwa related to bitcoin.